EDUKASI DAN KUANTIFIKASI FUNGSI EKOLOGIS PROGRAM BAMBOO CORNER SEBAGAI PENAHAN EROSI OLEH PT INDONESIA POWER SAGULING POMU - Salsabila, Alfira; Rosyidah, Ummi; Sofiyah; Kurniawan, Taufan (Jurnal Kelola: Jurnal Ilmu Sosial, 2022)
Saguling Dam is one of the large dam in the Citarum Watershed. Soil erosion in the watershed around the Saguling Dam can have very important ecological consequences, decreasing soil productivity and increasing sediment loads. Sediment resulting from erosion can settle and shallow the reservoir, thereby reducing the life of the dam. PT Indonesia Power Saguling POMU has made a social and environmental innovation, namely the Bamboo Corner program as a form of CSR program since 2017. Bamboo planting areas are carried out in 4 villages around the Saguling Dam, consist of Sirnagalih, Cijenuk, Mekarsari, and Sirnajaya villages. The four villages are included in the watershed area which empties into the Saguling Reservoir, so that bamboo planting is a natural preventive measure for soil erosion. Erosion rate analysis on each land unit was carried out using the Universal Soil Loss Equation (USLE) method. The data used in this study are secondary data, consist of rainfall data, administrative maps, soil type maps, slope maps, and land cover maps. The results showed that the weighted average erosion rate for the four villages was 552.99 tons/ha/year, so it was classified as a very heavy erosion rate. Bamboo planting has a significant effect in reducing the rate of erosion by 50% when compared to field land cover, namely bamboo plants are able to withstand the rate of erosion in the four villages of 232.44 tons/ha/year.